How lignin sticks to cellulose—insights from atomic force microscopy enhanced by machine-learning analysis and molecular dynamics simulations. Issue 47 (8th November 2022) - Nascimento, Diego M.; Colombari, Felippe M.; Focassio, Bruno; Schleder, Gabriel R.; Costa, Carlos A. R.; Biffe, Cleyton A.; Ling, Liu Y.; Gouveia, Rubia F.; Strauss, Mathias; Rocha, George J. M.; Leite, Edson; Fazzio, Adalberto; et al.
Abstract : Elucidating cellulose–lignin interactions at the molecular and nanometric scales is an important research topic with impacts on several pathways of biomass valorization. Abstract : Elucidating cellulose–lignin interactions at the molecular and nanometric scales is an important research topic with impacts on several pathways of biomass valorization. Here, the interaction forces between a cellulosic substrate and lignin are investigated. Atomic force microscopy with lignin-coated tips is employed to probe the site-specific adhesion to a cellulose film in liquid water. Over seven thousand force-curves are analyzed by a machine-learning approach to cluster the experimental data into types of cellulose-tip interactions. The molecular mechanisms for distinct types of cellulose–lignin interactions are revealed by molecular dynamics simulations of lignin globules interacting with different cellulose Iβ crystal facets. This unique combination of experimental force-curves, data-driven analysis, and molecular simulations opens a new approach of investigation and updates the understanding of cellulose–lignin interactions at the nanoscale.